Alokasi dan Pemanfaatan Kompensasi Pembayaran Jasa Lingkungan Air Kota Cirebon dan Kabupaten Kuningan - Tommi Febrian; Yusman Syaukat; Meti Ekayani (Jurnal Ilmu Pertanian Indonesia, 2018)
In recent years there has been a decrease in Cipaniis springs, indicating the declining ecological conditions of the area surrounding the spring. The compensation fund provided by Kota Cirebon to Kuningan Regency in the framework of payment for environmental services cooperation since 2004 has not provided significant benefits for Cirebon City, the surrounding community, and the environment. This study aims to evaluate the allocation and use of compensation funds and its benefits to the city of Cirebon, society, and the environment. Gap analysis is used to evaluate the allocation and use of compensation funds, as well as descriptive analysis on see the benefits of compensation funds for PDAM of Cirebon City, communities, and the environment. In 2016 the compensation fund paid is IDR 2.9 billion, of which only 16.23% is allocated for conservation activities, 1.53% for the villages around the springs and the remaining 82.3% for the Regional Government of Kuningan Regency. The compensation fund for the payment of environmental services has not been utilized properly, so the benefits received by PDAM of Cirebon City, society, and environment are still very low.